Engagement of students in writing when using strategies from mentor authors - Pumper, Sara (My University, 2013)
Teachers are continually looking for ways to motivate their students to become more engaged while writing. This action research focused on the incorporation of mentor author(s) into a kindergarten classroom writer's workshop. The first study compared the volume and complexity of students' writing before and after the inclusion of a mentor author. The results of this study showed that the volume of students' writing increased, as well as complexity in terms of dialogue and more punctuation. The study also demonstrated an increase in students' time on task while writing after the use of mentor texts. The second study looked more in depth at the time spent on task writing while incorporating a mentor text into the writer's workshop mini lesson. The results of this study showed that students were more engaged in their writing after listening to a mentor text read aloud during the mini lesson at the beginning of the writer's workshop time.
Plan B Paper. 2013. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 27 leaves. Includes bibliographical references (leaves 26-27).
Keywords: Language arts (Kindergarten); English language--Composition and exercises--Study and teaching